OPTIMIZATION OF PHYSICAL AND NUTRITIONAL FACTORS FOR ENHANCED PRODUCTION OF LIGNIN PEROXIDASE BY GANODERMA LUCIDUM IBL-05 IN SOLID STATE CULTURE OF WHEAT STRAW - S. Batool; M. Asgher; M. A. Sheikh; S. U. Rahman (Journal of Animal and Plant Sciences, 2013)
Microorganisms are commonly used in biotechnological and environmental processes through exploitation of their natural catalytic activities. An indigenous white rot fungus Ganoderma lucidum IBL-05 was used in solid state fermentation (SSF) of wheat straw for lignin peroxidase (LiP) production. The SSF process for LiP production was improved by optimizing some physical and nutritional parameters at pre-optimized pH 4.5 and temperature 35oC. By optimization different physical and nutritional factors, LiP production by the fungus was substantially improved to 1019 IU/mL after 48h in nutrient Medium III with 60% moisture level, 5mL inoculum size, glucose and urea as carbon and nitrogen sources in 15:1 C/N ratio, 1mL of 2mM Zn2+as metal ion and 1mL of 4mM 4-MMA as mediator. Surfactants like Tween-80, Tween-20 and SDS suppressed LiP synthesis by G. luucidum IBL-05.
Keywords: Ganoderma lucidum IBL-05; Wheat straw; Lignin peroxidase (LiP); solid state fermentation; optimization